THE USE OF PATH ANALYSIS IN THE DETERMINATION OF ENVIRONMENTAL FACTOR EFFECTS ON THE TOTAL PRODUCTION OF AQUACULTURE PONDS IN PASURUAN, EAST JAVA PROVINCE - Andi Indra Jaya Asaad; Erna Ratnawati; Akhmad Mustafa (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Environmental factors in the form of soil and water quality are the important factors of aquaculture pond productivity, including total production (tiger shrimps, Penaeus monodon, and milkfish, Chanos chanos) in Pasuruan, East Java Province. The objective of this study was to analyze the direct or indirect effects of soil and water quality on the total production of ponds in Pasuruan using a path analysis application. Data were collected in the pond areas around Pasuruan Regency including Nguling, Lekok, Rejoso, Keraton, and Bangil Sub-Districts as well as Pasuruan City. Soil quality was determined as a free variable and exogen; water quality as mediate variable, suspended, and endogen; as well as milkfish production as suspended variable and endogen. Environmental characteristics were illustrated using descriptive statistics, while environment factor effects on total production were analyzed using path analysis. The results of path analysis show that from the 12 analyzed soil quality variables, only two variables were affected in the total production of pond (tiger shrimps and milkfish) namely: contents of soil organic carbon and soil phosphate. While based on 11 water quality variables, two variables (water salinity and water iron) were affected the total production of ponds in Pasuruan Regency. The direct effects of soil organic carbon and phosphate on the total production were 0.314 and -0.600, respectively. Water salinity and water iron gave direct effects on total production amounting to -0.678 and 0.358 respectively. It is also found that two soil variables which were affected in the total production, did not indicate the effect towards water quality in ponds. Further implication of this research is put more attention for these variables into pond’s management in order to gain more production. Technical application could be appropriate for pond preparation and frequently water changing during grow out.